Identification and characterization of a Mycoplasma hyopneumoniae adhesin. - Zhang, Q (1995)
An adhesin of Mycoplasma hyopneumoniae was identified and characterized in this study. A monoclonal antibody (MAb), F2G5, and its F(ab')2 fragments inhibited the adherence of M. hyopneumoniae to porcine tracheal cilia, the natural targets to which the mycoplasma binds during infection. MAb F2G5 detected multiple bands, but predominantly recognized a 97-kDa (P97) protein of M. hyopneumoniae on immunoblots. Affinity chromatography, conducted with immobilized MAb F2G5, mainly purified P97. The purified proteins were able to bind to cilia and blocked the adherence of intact M. hyopneumoniae cells to cilia. Immunolabeling of mycoplasmas with MAb F2G5 under electron microscopy demonstrated that the proteins recognized by MAb F2G5 were located at the surface of the mycoplasma, predominantly on a surface fuzzy layer. These results indicate that P97 functions as an adhesin of M. hyopneumoniae. The N-terminal amino acid sequence of P97 did not have significant homology with any known bacterial or mycoplasmal adhesins, suggesting that P97 is a novel protein. The predominant proteins detected by MAb F2G5 in different strains varied in size, indicating that the antigen bearing the epitope for MAb F2G5 undergo intraspecies size variation. Antigenic variation of adhesins may be a pathogenic mechanism utilized by M. hyopneumoniae to evade the porcine immune system.